ANALISIS SISTEM AGROINDUSTRI TEH GAHARU (AQUILARIA MALACCENCIS L.) (STUDI KASUS CV BUMI HARUM DI KABUPATEN OGAN KOMERING ULU TIMUR) - Sinta Erviana; adia nugraha; Rabiatul Adawiyah (Lampung University, 2022)
The study aims to analyze raw material inventory management of agarwood tea, profits of agarwood tea, and the product distribution pattern in CV Bumi Harum, East Ogan Komering Ulu Regency, South Sumatra. The research method used is a case study by determining the location of the research purposively (deliberately). Data collection was by means of question and answer session using a questionnaire and observation carried out in December 2021 - January 2022. The analytical methods used were quantitative descriptive analysis (EOQ and profit analysis) and qualitative descriptive analysis (distribution patterns of agarwood tea). The results of this study are the optimal amount of stock of agarwood leaves based on the EOQ method is 155 kg per order with a frequency of 24 orders per year. The profit obtained by the agarwood tea CV Bumi Harum agroindustry per production is IDR2,279,629.12 with a product selling price of IDR10,000.00 per box. The pattern or distribution channel for agarwood tea at CV Bumi Harum consists of two channels, namely from CV Bumi Harum to consumers and from CV Bumi Harum to retailer and then to consumers. Keywords: agarwood tea, agroindustry, EOQ, profit